Influence of electrical impacts on the device characteristics of organic solar cells with a nanostructure electrode - Калманова , Д. М.; Сарбаева, С. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The integration of light capture properties and the use of plasmon effects of metal nanostructures are promising approaches for increasing the efficiency of energy conversion of organic solar cells. The effect of these approaches on improving light absorption has been extensively studied, especially in inorganic devices. Although this concept of light capture can be transferred to organic devices, it is also necessary to take into account the electrical effects caused by the nanostructure on the device’s performance due to the fundamental difference in the properties of organic semiconductor materials compared to their inorganic counterparts. In this contribution, as an example, we simulate the electrical properties of organic solar cells with a rectangular lattice structure compared to planar reference devices. Based on our numerical results, we demonstrate that, in addition to increasing optical absorption, the fill factor of the device is significantly improved due to the introduction of lattice structures. From the simulation, we came to the conclusion that the increased carrier collection efficiency is the main reason for the increase in the fill factor of the solar cell. This work contributes to a more fundamental understanding of the effect of nanostructured electrodes on the electrical properties of organic solar cells.